The Influence of Digital Payment Methods and Service Quality on Sales Volume at PT. Belanja Online Ekspress Nusantara - Tjuang, VALESIA TJUANG; Desma Erica Maryati M; Lisa Elianti Nasution (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
PT. Belanja Online Ekspres Nusantara is a company that operates in the e-retail sector of various types of general products such as household products. The phenomenon that occurs at PT. Express Nusantara's online shopping is currently the company's sales volume is still not in line with the desired expectations and the number of consumers who visit online also continues to decline every year. The purpose of this study was to determine the effect of The Influence of Digital Payment Methods and Service Quality on Sales Volume at PT. Belanja Online Ekspress Nusantara. Data collection techniques using a questionnaire. The population used is all consumers who make purchases at PT. Belanja Online Ekspress Nusantara during the 2022 period, the exact number of which is not known. In connection with the unknown population size, the sampling technique uses the Hairs formula where the number of indicators is 11indicators multiplied by 10 to obtain the maximum sample so that a total of 110 research samples are obtained. The research method uses quantitative descriptive. The data analysis technique used is multiple linear regression analysis which is Y = 1,204 + 0,433 X1 + 0,309X2 + e. In the Digital Payment variable (X1) it can be seen that the value of tcount(7.869) > ttable (1.981) with a significance of 0.000 < 0.05 so it can be concluded that there is a significant positive influence between Digital Payments on Sales Volume. In the Service Quality variable (X2), it can be seen that the value of tcount (7.045) > ttable (1.981) with a significance of 0.000 < 0.05 so it can be concluded that there is a significant positive influence between Service Quality and Sales Volume. Based on the table above, it is known that the value of Fcount (61.572) > Ftable(3.08) with a significance level of 0.00 < 0.05 so it can be concluded that there is a significant influence between Digital Payments and Service Quality on Sales Volume. The adjusted R Square (R2) value is 0.526. This means that the influence of Digital Payments and Service Quality on Sales Volume is: 52.6% and the remaining 47.4% is influenced by other factors originating from outside this research model.